A Multisite Evaluation of Pediatric Asthma-Related Treatment in Accordance to the 2007 National Heart, Lung and Blood Institute Expert Panel Report - 3 Guidelines - Emeka Oraka; Brittani Robinson; Trevor Ousley; Francesca Lopez; LeRoy Graham (Georgia Southern University, 2015)
Background: To determine if Georgia-based healthcare providers who received continuing education on pediatric asthma as described by 2007 National Heart, Lung, and Blood Institute Expert Panel Report - 3 guidelines demonstrated improvements in asthma-related treatment. Methods: We used a multi-site, cross-sectional design. Data were collected via surveys administered to healthcare providers and via randomized medical chart abstractions. Chart abstraction occurred at 12 months prior to intervention (n = 149); one month post-intervention (n = 208); and three months post-intervention (n = 123). Results: Substantial improvements were observed among the providers who used pre/post bronchodilator spirometry (5% at baseline, 12% at one month, and 19% at three months), and there was a significant increase in the number of patients being advised to improve conditions at home or school to avoid asthma triggers (9% at baseline, 43% at one month, and 37% at three months). However, prescription of preventive medications and patients being taught proper medication/spacer technique by providers decreased from baseline to three-months (69% vs 55% and 41% vs 27%, respectively). Providers' self-reported barriers and patient load were consistently associated with poorer treatment outcomes. Healthcare providers who received continuing education on NHLBI - EPR 3 guidelines demonstrated an increase in spirometry use and in advising patients on improving home and school conditions. While these findings are useful, provider-reported barriers such as time, organizational, and insurance barriers prevent providers from effectively systematically incorporating all of the EPR 3 guidelines. Conclusions: Internal efforts to address clinical barriers combined with continued education may result in improvements in pediatric asthma-related treatment outcomes.